2022
DOI: 10.1128/msphere.00913-21
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SARS-CoV-2 in Nasopharyngeal Samples from Patients with COVID-19 Illustrates Population Variation and Diverse Phenotypes, Placing the Growth Properties of Variants of Concern in Context with Other Lineages

Abstract: SARS-CoV-2 is the causative agent of COVID-19. The virus has spread across the planet, causing a global pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…SARS-CoV-2 variants display various degrees of transmissibility and confer differing levels of disease severity in infected patients (Harvey et al, 2021; 10.3389/fmicb.2022.997539 10.3389/fmicb.2022.997539 -Pastrana et al, 2022). Moreover, studies have shown that SARS-CoV-2 variants have different replication rates and produce distinct viral titers from infected Vero cells (Jeong et al, 2021;Prince et al, 2022). Because inhibition of stress granule formation is related to viral replication (McCormick and Khaperskyy, 2017), we hypothesized that SARS-CoV-2 variants might also show differing degrees of stress granule inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 variants display various degrees of transmissibility and confer differing levels of disease severity in infected patients (Harvey et al, 2021; 10.3389/fmicb.2022.997539 10.3389/fmicb.2022.997539 -Pastrana et al, 2022). Moreover, studies have shown that SARS-CoV-2 variants have different replication rates and produce distinct viral titers from infected Vero cells (Jeong et al, 2021;Prince et al, 2022). Because inhibition of stress granule formation is related to viral replication (McCormick and Khaperskyy, 2017), we hypothesized that SARS-CoV-2 variants might also show differing degrees of stress granule inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The second method, DiversiTools (code available at https://github.com/josephhughes/DiversiTools ), uses the primer-trimmed alignment file (named as [sampleID]_L001.final.bam) and its associated index file (produced in the EasySeq pipeline) along with the reference genome and a coding region file to analyse the minor genomic variation and predict the amino acid sequence based on the genomic data. DiversiTools allows for an in-depth analysis of viral diversity in each sample, rather than just the consensus/dominant genomic information, as previously described 17 . Participants were included in the minor variant analysis if all three of their samples met the following criteria: 1) the dominant genome sequence had a minimum 90% consensus called and 2) 90% of genome positions had a minimum coverage of 200X.…”
Section: Methodsmentioning
confidence: 99%
“…Vero hSLAM cells that express the human signalling lymphocytic activation molecule (SLAM) 14 , and VAT cells -Vero E6 expressing both human angiotensin-converting enzyme 2 (ACE2), the major receptor of SARS-CoV-2, and transmembrane serine protease 2 (TMPRSS2), which cleaves the viral S protein priming it for cellular infection 15 . Both viral growth kinetics and changes to cell morphology (i.e., cytopathic effects; CPE) can vary between these different cell lines thereby impacting the outcome of tests used to assess culture positivity 16 . For example, a 2020 study found that cell culture supernatants from Vero E6 cells expressing TMPRSS2 had more than 100 times more viral RNA copies than Vero E6 cells not expressing this protein 17 .…”
Section: Introductionmentioning
confidence: 99%